Race & rhyme : rereading the New Testament - Sechrest, Love L., 1962- (Grand Rapids Wm.B. Eerdmans Publishing, 2022)
"A reading of select New Testament texts in dialogue with modern-day issues of racial justice through an approach the author terms "associative hermeneutics.""--
Includes bibliographical references (pages 327-362) and indexes.
Keywords: Bible. -- Hermeneutics; Bible. -- Criticism, interpretation, etc; Racial justice -- Biblical teaching